Steviol glycosides enhance pancreatic beta-cell function and taste sensation by potentiation of TRPM5 channel activity - Philippaert, K; Pironet, A; Mesuere, M; Sones, W; Vermeiren, L; Kerselaers, S; Pinto, S; Segal, A; Antoine, N; Gysemans, C; Laureys, J; Lemaire, K; et al. (Nature Publishing Group, 2017)
Steviol glycosides (SGs), such as stevioside and rebaudioside A, are natural, non-caloric sweet-tasting organic molecules, present in extracts of the scrub plant Stevia rebaudiana, which are widely used as sweeteners in consumer foods and beverages. TRPM5 is a Ca(2+)-activated cation channel expressed in type II taste receptor cells and pancreatic β-cells. Here we show that stevioside, rebaudioside A and their aglycon steviol potentiate the activity of TRPM5. We find that SGs potentiate perception of bitter, sweet and umami taste, and enhance glucose-induced insulin secretion in a Trpm5-dependent manner. Daily consumption of stevioside prevents development of high-fat-diet-induced diabetic hyperglycaemia in wild-type mice, but not in Trpm5(-/-) mice. These results elucidate a molecular mechanism of action of SGs and identify TRPM5 as a potential target to prevent and treat type 2 diabetes.